Core-shell structured silk Fibroin/PVDF piezoelectric nanofibers for energy harvesting and self-powered sensing - Siqi Wang; Kunming Shi; Bin Chai; Shichong Qiao; Zhuoli Huang; Pingkai Jiang; Xingyi Huang (Nano Materials Science, 2022)
The development of wearable and portable electronics calls for flexible piezoelectric materials to fabricate self-powered devices. However, a big challenge in piezoelectric material design is to boost the output performance while ensuring its flexibility and biocompatibility. Here, all-organic and core-shell structured silk fibroin (SF)/poly(vinylidene difluoride) (PVDF) piezoelectric nanofibers (NFs) with excellent flexibility are fabricated using a simple electrospinning strategy. The strong intermolecular interaction between SF and PVDF promotes the β-phase nucleation in the core-shell structure, which significantly enhances the output performance. An output of 16.5 ​V was achieved in SF/PVDF NFs, which is more than 6-fold enhancement compared with that of pure PVDF NFs. In addition, the piezoelectric device can sensitively detect the mechanical stimulation from joint bending, demonstrating its great potential in self-powered sensor. Otherwise, the piezoelectric device can be also applied to control the movement of a smart car, successfully, achieving its application in the human-machine interaction.